Health Profile of Elderly Persons in Urban and Rural Field Practice Areas of Medical College Himmatnagar, Gujarat - Kavita Banker; Bipin J Prajapati; Jignesh Chauhan (Medsci Publications, 2018)
Background: Care of old age people is becomes a big social problem due to urbanization, nuclearisation of family, migration, and dual career. The objective of this study was to assess socio-demographic condition and health problems among elder people in rural and urban population. Methods: This cross-sectional study was carried out in RHTC and UHTC of a Medical College in Himmatnagar during Jan to Sept 2016. House to house survey was carried out and 175 elder individual more than 60 years age were included in the study. Results: 34.9% & 64.6% participants were illiterate and 13.4% % 8.0% were residing alone, 17.2% & 32.6% had restricted mobility, 30.3% & 38.3% had inadequate sleep problems, 22.9% & 27.4% was overweight, higher blood pressure among 57.14% & 37.71%in rural and urban area respectively and mean BMI was 22.9 ± 12.82 & 23.59 ± 4.68 in rural and urban area respectively. Conclusion: Major requirement for interventions to ensure the health of this susceptible group and to initiate a policy to address the care and needs of the disabled elderly.